1997
DOI: 10.1007/pl00005751
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of surround inhibition in cat area 17

Abstract: The effects of stimuli falling outside the 'classical receptive field' and their influence on the orientation selectivity of cells in the cat primary visual cortex are still matters of debate. Here we examine the variety of effects of such peripheral stimuli on responses to stimuli limited to the receptive field. We first determined the extent of the classical receptive field by increasing the diameter of a circular patch of drifting grating until the response saturated or reached a maximum, and by decreasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
203
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(240 citation statements)
references
References 25 publications
31
203
4
Order By: Relevance
“…For low-contrast central stimuli, surround stimuli cause facilitation, whereas for high-contrast central stimuli, surround stimuli cause suppression (Polat et al 1998;Sengpiel et al 1997;Toth et al 1996). The facilitation is thought to depend on depolarizing synaptic inputs that can be evoked by stimuli outside the classical receptive field, as demonstrated by whole cell recordings (Bringuier et al 1999) and by imaging (Toth et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For low-contrast central stimuli, surround stimuli cause facilitation, whereas for high-contrast central stimuli, surround stimuli cause suppression (Polat et al 1998;Sengpiel et al 1997;Toth et al 1996). The facilitation is thought to depend on depolarizing synaptic inputs that can be evoked by stimuli outside the classical receptive field, as demonstrated by whole cell recordings (Bringuier et al 1999) and by imaging (Toth et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In primary visual cortex and primary somatosensory cortex, context-dependent enhancement and suppression appear to depend on the relative level (or contrast) of the probe (Levitt and Lund 1997;Moore et al 1999;Polat et al 1998;Sengpiel et al 1997;Toth et al 1996). For high-level or high-contrast probes, contextual stimuli tend to cause suppression.…”
Section: Introductionmentioning
confidence: 99%
“…However, note that the former case is rarely found, since carrier orientation tunings for the CRF and surround are usually similar (Akasaki et al 2002;Blakemore and Tobin 1972;Nelson and Frost 1978;Walker et al 1999). Even if a neuron is more effectively suppressed by nonoptimal CRF orientations, it is likely that this neuron is suppressed by the CRF preferred orientation to some degree (Sengpiel et al 1997).…”
Section: Consideration On the Present Methods In Comparison With Othermentioning
confidence: 99%
“…Although the initial studies suggested that the responses of primary visual cortex (V1) neurons to an optimal stimulus are suppressed selectively by masking stimuli of orthogonal orientation, a consensus has emerged that a wide range of orientations can cause suppression, both within and outside the classical receptive field, with surround suppression in fact being strongest at the optimal orientation of the cell (Bonds, 1989;Nelson, 1991;DeAngelis et al, 1992;Li and Li, 1994;Sengpiel et al, 1997).…”
Section: Introductionmentioning
confidence: 99%